ANALISIS YURIDIS KEBERADAAN PERUSAHAAN OUTSOURCING DAN HAK PEKERJA TERKAIT SISTEM KONTRAK BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 - Haerudin .; Endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2021)
The purpose of this study are: 1) To find out and analyze the existence of outsourcing companies in contract system workers. To find out and analyze the granting of rights for workers related to the contract system based on Law No. 13 of 2003 concerning Labor. The research method used in this study is a normative juridical study that takes a qualitative approach that looks at and analyzes the legal norms in existing legislation and sociological research as supplementary data as primary data. The results of this study are: 1) The existence of outsourcing companies in contra system workers, in terms of employment relations between workers and outsourcing companies is based on a Specific Time Work Agreement, then the work agreement must require the transfer of the protection of the rights of workers whose objects of work remain, even though there is a change of companies that carry out part of the work of other companies or companies providing workers' services. 2) The granting of rights for workers related to the contract system based on Law Number 13 of 2003, there are still outsourced workers who are not registered with Jamsostek, so the legal protection of health and safety for outsourced workers is not implemented.Keywords : Labor Law; Outsourcing Company; Work Agreement.